(untitled) (Revista Chilena de Rehabilitación y Actividad Física, 2025)
During adolescence, it is essential to practice physical activity to improve overall health. According to the World Health Organization, more than 390 million young people are overweight or obese. Aerobic games stand out as an effective way to promote emotional balance and improve physical activity. The objective was to evaluate the effect of aerobic games on cardiorespiratory capacity and their effects on anxiety. The study has a longitudinal experimental design, the sample was 57 students randomly divided into two groups, experimental (28 students) and control (29 students) to whom the 6-minute walk test and Beck’s anxiety test were applied pre- and post-intervention. During 8 weeks, a weekly session of 45 minutes was applied, the results showed statistically significant improvements in the various variables evaluated, in the maximum oxygen consumption (VO₂ max.) increased the mean from 2768.7 ml/min to 2924.8 ml/min, with a standard deviation (SD) reduced from 998.0 to 925.2, reflecting statistically significant differences (p < 0.001). Similarly, test anxiety decreased from 22.7 to 18.3 and SD 14.4 to 12.5, also showing considerable statistical significance (p < 0.001). It is concluded that a program of aerobic games with a duration of 8 weeks generates positive effects on cardiorespiratory capacity and also reduces the anxiety levels of the students. This research has important implications for the promotion of physical activity in adolescents.